IMPROVING STUDENTS’ VOCABULARY BY USING ANIMATION VIDEO AT THE SEVENTH GRADE OF SMP GPdI BEREA TONDANO - Elisabet Lasmaria Hutasoit; Elisabeth Z. Oroh; Merlin Maukar (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The goal of this research is to determine whether or not using animation videos can improve students' vocabularies. The students of SMP GPdI BEREA Tondano, specifically the 20 students in seventh grade, were selected as the study's subject. One group had pre- and post-tests as part of the pre-experimental design used in this study. Two meetings were needed to complete the study. The research first provides a pre-test, the treatment, and a post-test. The method of data collection uses a multiple-choice test with 20 options as the instrument. This study's findings demonstrate that animation videos can increase students' vocabulary, as evidenced by the higher post-test scores than pre-test scores. The mean pre-test score is 31.5 and the mean post-test score is 80. It is true that watching animated videos can improve kids' vocabularies.